ChemInform Abstract: Hauser—Heck: Efficient Synthesis of γ‐Aryl‐β‐ketoesters en Route to Substituted Naphthalenes. Issue 14 (March 2016) - Wagner, Frederic; Harms, Klaus; Koert, Ulrich
Abstract: A wide range of the title ketoesters is easily accessible in one step from various aryl bromides and bis(trimethylsilyl) enol ethers using a novel Hauser—Heck combination.